Friction Dynamics on Human Skin Surfaces - Nonomura, Yoshimune; Ouchi, Haruka (Journal of Oleo Science, 2020)
This study includes an evaluation of friction on the fingers, palms, and forearms of 20 subjects using a sinusoidal motion friction evaluation system. The effects of the changing water content in the stratum corneum at each position as well as the skin elastic modulus on the friction parameters were analyzed to show the factors governing friction dynamics. We observed a significant delay time (δ) and a stick–slip phenomenon during the sinusoidal motion friction processes. These dynamic phenomena are due to the softness and viscoelastic properties of human skin. The findings regarding the response of human skin to frictional stimulation under accelerated conditions facilitates a better understanding of the dynamic and mechanical properties of human skin.